Guide to Fertilization for Pine Straw Production on Coastal Plain Sites - Anna Osiecka; Patrick J. Minogue; E. David Dickens (EDIS)
Pine straw has gained popularity as a mulch for residential and commercial landscaping in urban and suburban areas. It is attractive, relatively low-cost, and easy to work with. Best of all, it performs well in all kinds of locations–including those difficult-to-mulch slopes! Pine straw is perfect for water-efficient landscaping (xeriscaping), an increasingly popular choice for environmentally conscious landscapers. Thanks to the growing popularity of this natural mulch material, pine straw production has quickly become an important Florida industry. Regularly removing pine straw from pine stands is not without consequences, however; the loss of the cover and nutrients pine straw provides can reduce the productivity of the pine forest. Proper fertilization and harvest techniques are crucial to maintain the viability of the new industry and traditional pine industries alike. This 12-page guide explains how to fertilize wisely to offset the effects of pine straw removal and maintain the viability of pine plantations. Written by Anna Osiecka, Patrick J. Minogue, and E. David Dickens, and published by the School of Forest Resources and Conservation, December 2015.